Pemberdayaan Petambak Udang Vanamei melalui Implementasi Pembangkit Hybrid (Turbin angin-Panel surya) untuk mendukung Budidaya - Maulana, Frendi; Aritonang, Ridho; Maulita Purnama Sari, Eny; Mutmainah, Siti (Jurnal Pengabdian Masyarakat Ilmu Pendidikan, 2025)
This community service project addresses the high operational costs of Litopenaeus vannamei cultivation by implementing a hybrid power system combining a venturi wind turbine and solar panels. The methodology utilizes the Plan-Do-Check-Act (PDCA) cycle to ensure active community participation and promote technology adoption, which is a key factor for the program's long-term success and sustainability. Economically, this implementation resulted in substantial benefits, demonstrating a 36.47% decrease in fuel expenses (Rp 1,399,000) and an overall operational cost efficiency of Rp 4,021,500. This efficiency effectively improved aquaculture profitability, with profit increasing from Rp 15,071,938 to Rp 15,969,750. Thus, the project offers a concrete, efficient, sustainable, and environmentally friendly solution for shrimp cultivation.